Pelatihan Pemasaran Digital Kelompok Peternak Lebah Trigona Ampel Mesari Banjar Bebali Desa Berembeng - I Gusti Ngurah Satria Wijaya; Ketut Gus Oka Ciptahadi; Laser Narindro (BEKTI : Jurnal Pengabdian kepada Masyarakat, 2023)
The Trigona Beekeepers Group "Ampel Mesari" is a collective of trigona beekeepers that accommodates farmers in the Banjar Be-bali region, Berembeng Village. The issue faced by this group is that the marketing process is still conducted conventionally by spreading information or promotions through word of mouth. The problem-solving approach provided by this community service program involves offering digital marketing training through a profile website. The implementation method of this community service activity includes socialization activities, core training sessions, and monitoring and evaluation. The execution of digital marketing training activities proceeded smoothly. It can be concluded that there was knowledge transfer, especially in digital marketing, indicated by improved test results. Participants responded positively and enthusiastically to the training, encountering no obstacles in comprehending the training material.